Vibration Control of AMB-Rotor System Under Base Motions Based on Disturbance Observer - Zhang, Yue; Xu, Yuanping; Zhou, Jin; Zhou, Yang; Mahfoud, Jarir (IEEE/ASME transactions on mechatronics, 2025)
Active magnetic bearings (AMBs) can actively control the on-board rotor to reduce excessive vibration caused by base motion and improve the system's ability to withstand base excitation. Current active controllers for base motions require additional sensors or complex robust designs, making it difficult to balance reliability and applicability. In this article, a disturbance observer (DOB) approach is developed, numerically and experimentally, to observe and suppress disturbance caused by base motions, which can achieve vibration control without adding additional sensors or replacing the commonly used proportional-integral-derivative controller. Specifically, an AMB-rotor system model considering base motions is established based on general equation of motion. The effect of base motions on the system is considered as disturbance, including additional external forces, stiffness forces, and gyroscopic forces. The working principle, robust stability analysis, and design process of the DOB are presented. Simulation and experiments are conducted on a lab-scale AMB-rotor test rig. The DOB exhibits satisfactory behaviors under harmonic and shock excitations. The impact of the observation bandwidth of the DOB on vibration suppression is also analyzed.